Survey of the caries rate in children aged 6 to 8 in a public school in the municipality of Pindamonhangaba-SP, Brazil (Research, Society and Development, 2025)
The high prevalence of caries in children is, unfortunately, a reality in several regions of the country, and the main contributing factors are inadequate oral hygiene and lack of access to treatment and dental follow-up. The present study aimed to organize data on the rate of caries lesions in children from 6 to 8 years old at a public school in the city of Pindamonhangaba-SP, Brazil, in order to evaluate the current panorama of the disease and raise discussions about the prevalence of caries. The research was observational, with data collection carried out during a social action promoted by the Rotary Club in partnership with the course of dentistry at the UniFunvic University Center. We evaluated 87 children, students of a municipal school. It was possible to verify that 42.86% of boys presented caries, while among girls the prevalence was 57.78%, showing a higher occurrence in females.  The specific analysis of the first permanent molars revealed that, among children with these erupted teeth, 11.36% of girls and 5.13% of boys had caries lesions. The data obtained in this survey reinforce the importance of the continuity of oral health promotion and prevention actions within the school environment. It was concluded with this study that the evaluated child population has a high prevalence of caries, affecting more than half of girls and almost half of boys, in addition to permanent first molars lesions. There was a strong relationship with socioeconomic factors, showing that specific actions are not enough.